Effect of Time Pressure, Audit Risk and Materiality to Disclosure Prematures to Audit Procedures - Maria Angelina Yauwtanthy (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
Premature sign-off of audit procedure is one form of Reduce Audit Quality Behavior/RAQ. The purpose of the research is to examine and analyze the influence time pressure, audit risk and materiality to premature sign-off of audit procedures.The respondent of this research are auditors who working at Public Accountant Firms in DKI Jakarta. This reseearch used SPSS 21 (Statistical Product and Service Solutions). The result of this research are time pressure, audit risk and materility have an influence to premature sign-off of audit procedures simultaneously.Time pressure doesn’t have significantly influence to premature sign-off of audit procedure, but audit risk have significantly influence to premature sign-off of audit procedure and materiality have a negative influence to premature signI Hey Hey -off of audit procedure